PROFESI ADVOKAT: ANTARA HARAPAN DAN KENYATAAN - Solehoddin Solehoddin (Widya Yuridika, 2018)
Lawyer is a honourable profession (officum nobile). And in doing so, he should work under the protection of law, regulation, and ethical codes, and he has freedom on the basis of this respect and personality. As a lawyer namely self-help, sincerity, and openness. He works as a law enforcers having equivalent position with judges, policemen, or attorneys. In fact, in its development, this profession encounters many challenges. For example, the people underestimate this profession since those working on this field show improper behaviors which are irrelevant with the ethical codes. It is not wrong if there is a stigma in this profession that a lawyer is a “junk profession”. Kata kunci: Profesi hukum, dan advokat